Case report: A rare congenital esophageal malformation on double esophagus in the rat - Canpolat, Leyla; Sa?iro?lu, Oya; Kükner, Aysel; Ozan, Enver (My University, 1998)
A double esophagus was coincidently observed in one male rat among 'a group of Wistar adult rats used for histological studies. This is apparently the first case reported in the rat and other animals.
Keywords: Esophagus; Malformation